Depth and breadth characteristics of Indonesian vocabulary among Thai university students: A multidimensional analysis of lexical knowledge - Ulfa Kurniasih; Azizatul Khairi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Vocabulary mastery in second language acquisition encompasses both breadth (the number of words known) and depth (the quality of lexical knowledge, including semantic relations and collocations). This exploratory study investigates the characteristics of Indonesian vocabulary breadth and depth among ten Thai students enrolled in the BIPA program at UIN K.H. Abdurrahman Wahid Pekalongan. Given the small and purposive sample, findings are contextual and exploratory rather than generalizable. Using a mixed-methods explanatory sequential design, the study employed the Vocabulary Size Test (VST) for breadth and the Word Associates Test (WAT) for depth measurement, supplemented by semi-structured interviews. Results reveal a moderate vocabulary size with strong mastery of high-frequency words but substantial gaps in academic and low-frequency vocabulary. Depth profiles were uneven: synonym knowledge was comparatively stronger, while collocational competence—particularly idiomatic collocations—was markedly weak. Pattani Malay lexical transfer emerged as the primary source of collocational errors. These findings carry pedagogical implications for differentiated vocabulary instruction in BIPA, particularly through the development of academic vocabulary learning strategies and explicit collocation teaching informed by contrastive analysis of Pattani Malay and Indonesian.